Comparing Increasing Tryptophan:Lysine Ratios in DDGS-Based Diets with or without a DDGS Withdrawal Strategy on Growth Performance and Iodine Value of Growing-Finishing Pigs - Mikayla S. Spinler; Andres F. Tolosa; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Kyle F. Coble; Brittany A. Carrender; Amanda J. Gerhart; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 6,240 pigs (DNA 600 × PIC 1050; initially 49.7 × 2.23 lb), divided into 2 groups, were used in a 119- or 120-d study to compare increasing the Trp:Lys ratio in diets with DDGS or a DDGS withdrawal strategy on growth performance and carcass fat iodine value of grow-finish pigs. Pigs were randomly allotted to 1 of 7 dietary treatments with 30 to 36 pigs per pen and 26 replications per treatment. Diets were fed in 4 phases (approximately 50 to 96, 96 to 157, 157 to 220, and 220 lb to market). Diets included a control corn-soybean meal-based diet formulated to a 19% SID Trp:Lys ratio; 4 diets with 30% DDGS fed in all four phases and formulated to achieve a 16%, 19%, 22%, or 25% SID Trp:Lys ratio, respectively; and 2 DDGS withdrawal strategy diets: 19% SID Trp:Lys with 30% DDGS in phases 1 through 3 and then 0% DDGS in phase 4 with either a 19 or 25% Trp:Lys ratio. Overall, BW, ADG, ADFI, and F/G improved (linear,P<0.05) as the SID Trp:Lys ratio increased in diets with 30% DDGS fed in all 4 phases. Hot carcass weight and carcass yield increased (quadratic,P<0.05) as the Trp:Lys ratio increased along with backfat depth (linear,P= 0.040). Pigs fed diets containing a SID Trp:Lys ratio of 19% and 30% DDGS from phases 1 through 3 and 0% DDGS in phase 4 had the greatest numeric ADG and ADFI for the overall study, but were not different than pigs fed the control, the 25% Trp:Lys withdrawal treatment, or the 30% DDGS diets with 25% Trp:Lys ratio throughout the study. Pigs fed the control diet had decreased (P<0.05) carcass fat iodine value compared to pigs fed DDGS throughout the study, with pigs fed the two DDGS withdrawal strategies having lower (P<0.05) iodine values compared to pigs fed 30% DDGS in all 4 phases. No significant differences (P>0.05) in revenue per pen or IOFC per pen were observed, however, feed cost per lb of gain (quadratic,P= 0.001) and feed cost per pig placed (linear,P= 0.002) increased and revenue per pig placed tended to increase (P= 0.064) as the Trp:Lys ratio increased. In summary, increasing the SID Trp:Lys ratio in diets with 30% DDGS resulted in a linear improvement in ADG, ADFI, F/G, and BW but did not influence iodine values. Removing DDGS from the diet in the last period reduced carcass fat iodine value and increased growth rate during the withdrawal period compared to pigs fed 30% DDGS throughout, indicating value in a withdrawal strategy.
Keywords: dried distillers grains with solubles; DDGS; finishing pig; tryptophan; withdrawal strategy